2006
DOI: 10.1111/j.1529-8817.2006.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

MORPHOLOGICAL AND MOLECULAR CHARACTERIZATION OF PLANKTONIC CYANOBACTERIA FROM BELGIUM AND LUXEMBOURG1

Abstract: For the first time in Belgium and Luxembourg, the diversity and taxonomy of 95 cyanobacterial strains isolated from freshwater blooms were assessed by the comparison of phenotypes and partial 16S rRNA gene sequences. The results showed the high diversity of nanoplanktonic, picoplanktonic, and benthic-periphytic cyanobacteria accompanying the main bloom-forming taxa. Indeed, besides 15 morphotypes of bloom-forming taxa, seven nonbloom-forming planktonic morphotypes and 11 morphotypes from benthic-periphytic tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 50 publications
10
90
2
5
Order By: Relevance
“…Moreover, the 23S rRNA gene displayed more polymorphisms than the 16S rRNA gene, which was virtually identical in virtually all isolates. The phylogenetic analysis of the 16S rRNA gene confirmed that all isolates belong to the Pseudanabaena/Limnothrix group with 99% cluster similarity (Zwart et al, 2005;Willame et al, 2006). From BLAST searches against the GenBank database, we observed that 42% of the isolates were 100% identical to Pseudanabaena sp.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Moreover, the 23S rRNA gene displayed more polymorphisms than the 16S rRNA gene, which was virtually identical in virtually all isolates. The phylogenetic analysis of the 16S rRNA gene confirmed that all isolates belong to the Pseudanabaena/Limnothrix group with 99% cluster similarity (Zwart et al, 2005;Willame et al, 2006). From BLAST searches against the GenBank database, we observed that 42% of the isolates were 100% identical to Pseudanabaena sp.…”
Section: Resultsmentioning
confidence: 61%
“…This cluster is commonly referred to as the Pseudanabaena/Limnothrix group (Gkelis et al, 2005;Willame et al, 2006). This group also comprised several environmental sequences as well as other isolates including the type strain Pseudanabaena PCC7408, strains belonging to L. redekei (Van Goor, Meffert) (Limnothrix sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study that focused on 12 heterocystous cyanobacterial genera and 41 cyanobacterial strains in total, the HIP primers and their resolution were found to be sufficient for estimating the phylogenetic relationships amongst heterocystous cyanobacteria. The dendrograms constructed using HIP fingerprints (HIP-AT, HIP-CA, HIP-GC, and HIP-TG) showed that the genus Nostoc was most genetically heterogeneous and advanced amongst all the 12 genera (Rajaniemi et al 2005;Svenning et al 2005;Willame et al 2006). One of the interesting features was the differential alignment of the strains Nostoc sp.…”
Section: Discussionmentioning
confidence: 99%